Efektivitas Penggunaan Model Pembelajaran Reciprocal Teaching Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Di MTs. AL-Mukhtariyah Sungai Dua Portibi - Siti Rokiah; Rahmatika Elindra; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study is to describe the effectiveness of using reciprocal teaching on students’ mathematical problem solving ability on the material system of two-variable linear equations at the eighth grade students of Mts. Al-Mukhtariyah Sungai Dua Portibi. The research was conducted by applying experimental method (one group pretest post test design) with 30 students as the sample and they were taken by using random sampling technique from 134 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using reciprocal teaching was 2.87 (good category) and (b) the average of students’ mathematical problem solving ability on the material system of two-variable linear equations before using reciprocal teaching was 65.25 (enough category) and after using reciprocal teaching was 85.7 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 16), the result showed the significant value was less than 0.05 (0.000<0.05). It means, using reciprocal teaching was effective used on students’ mathematical problem solving ability on the material system of two-variable linear equations at the eighth grade students of Mts. Almukhtariyah Sungai Dua Portibi.